Odpowiedzi

2010-02-22T17:54:08+01:00
A) 3(ײ-2x+3)-2(x²-5x-1)= dla x=2,
=3x²-6x+9-2x²+10x+2=3x²-2x²-6x+10x+9+2=x²+4x+11=
=2²+4*2+11=4+8+11=23
b) a(2ab+b)-b(a-ab+a²)= dla a= 0,1 dla b= -10
2a²b+ab-ba+ab²-a²b=2a²b-a²b+ab²=a²b+ab²=0,1²*(-10)+0,1*(-10)²=
=0,01*(-10)+0,1*100=-0,1+10=9,9
  • inqa
  • Rozwiązujący
2010-02-22T17:54:50+01:00
A) 3(ײ-2x+3)-2(x²-5x-1) dla x=2

3(x2-2x+3)-2(x2-5x-1)=3x2-6x+9-2x2+10x+2=x2+4x+11
x2+4x+11= 4+8+11=23

(niektore "2" znacza do potegi drugiej :)

b) a(2ab+b)-b(a-ab+a²) dla a= 0,1 dla b= -10
a(2ab+b)-b(a-ab+a2)=2a2b+ab-ab+ab2+a2b=3a2+ab2

3a2+ab2=3*0,1*(-10)+0,1*[(-10)*(-10)]=0,3*(-10)+0,1*100=-3+100=97
2010-02-22T17:58:52+01:00
A) 3x²- 6x+9 - (2x²-10x+2) = 3x²-6x+9 - 2x²+10x-2= x²+4x+7 = 4+8+7=19

b) 2a²b+ab - ab+ab²-a²b= a²b-ab²= -0,1 - 10 = -10,1